Memetakan Segmentasi Target Dan Positioning Produk Kuliner Untuk Perancangan Konten Instagram - Lathifah, Lailia; Wibowo, Sampurno (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Instagram content is growing rapidly and more and more business people are taking advantage of this opportunity to develop their business online. This research aims to map the segmentation, targeting, and positioning (STP) of Nasi Kebuli Al-Ghazali culinary products in Instagram content design. The method used is descriptive qualitative with a case study approach to the Nasi Kebuli Al-Ghazali MSME. The results showed that market segmentation includes West Java people with an age range of 20-60 years from various groups. The target market focuses on Islamic events and communities that love Middle Eastern specialties. Product positioning emphasizes the quality of raw materials and the health benefits offered. Instagram content design is focused on strengthening the brand image and increasing engagement with the audience.